Proton beam emittance growth in the Relativistic Heavy Ion Collider - S. Y. Zhang; V. Ptitsyn (Physical Review Special Topics. Accelerators and Beams, 2008)
With the significant beam intensity improvement in RHIC polarized proton run 2005 and run 2006, the emittance growth becomes a luminosity limiting factor. The beam emittance growth has a dependence on the dynamic pressure rise, which in RHIC proton runs is mainly caused by the electron cloud. The dependence of the emittance growth on other electron cloud related parameters is also identified. The beam instability is usually absent, and the emittance growth rate is much slower than the ones typically caused by the head-tail instability. It is suspected that the emittance growth is caused by the electron cloud below the instability threshold. A discussion follows.